2020
DOI: 10.3934/krm.2020024
|View full text |Cite
|
Sign up to set email alerts
|

Strong solutions for the Alber equation and stability of unidirectional wave spectra

Abstract: The Alber equation is a moment equation for the nonlinear Schrödinger equation, formally used in ocean engineering to investigate the stability of stationary and homogeneous sea states in terms of their power spectra. In this work we present the first well-posedness theory for the Alber equation with the help of an appropriate equivalent reformulation. Moreover, we show linear Landau damping in the sense that, under a stability condition on the homogeneous background, any inhomogeneities disperse and decay in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 30 publications
(65 reference statements)
1
22
0
Order By: Relevance
“…The Penrose criterion ( 14) can be numerically computed for any type of background. We recall here that the realistic spectra, when become narrow, switch to instability from stable state and vice versa happens when they become broader [27]. Hence in order to achieve our task, we consider only the narrow spectrum as background.…”
Section: Instability Arising Out Of Narrow Spectral Backgroundmentioning
confidence: 99%
“…The Penrose criterion ( 14) can be numerically computed for any type of background. We recall here that the realistic spectra, when become narrow, switch to instability from stable state and vice versa happens when they become broader [27]. Hence in order to achieve our task, we consider only the narrow spectrum as background.…”
Section: Instability Arising Out Of Narrow Spectral Backgroundmentioning
confidence: 99%
“…The Alber equation, its derivation and interpretation have been widely studied and explained. We refer readers who are interested to [23,[28][29][30] and the references therein for more details. Here, we will briefly present its derivation and main features in order to make the paper self-contained.…”
Section: Ocean Wave Modelling With the Alber Equationmentioning
confidence: 99%
“…This was called an "eigenvalue relation" in [23]; we will call it an "instability condition". In [30], it was further shown that if the instability condition does not hold, then linear stability follows. The instability condition (7) itself can be refined in two ways: One concerns a technical issue related to X " 0.…”
Section: The Stability-of-homogeneity Questionmentioning
confidence: 99%
See 2 more Smart Citations